Endothelial progenitor cells in the peripheral blood of patients with moyamoya disease labeled with superparamagnetic iron oxide in vitro for MRI detection - Wang,Xirui (2020)
Moyamoya disease (MMD) is currently thought to involve endothelial progenitor cells (EPCs). We investigated whether superparamagnetic iron oxide (SPIO) can be used to label EPCs. Mononuclear cells from 10 moyamoya disease patients were isolated, and cluster of differentiation 133 (CD133) positive cells sorted by magnetic-activated cell sorting were cultured in vitro. The positive rates of CD133, vascular endothelial growth factor receptor (VEGFR)-2, and cluster of differentiation 34 (CD34) were detected by flow cytometry. The cells were co-cultured with fluorescence labeled Dil-acetylated-low-density lipoprotein (Dil-ac-LDL) and Ulex europaeus agglutinin-1 (UEA-1) to observe the endocytosis of Dil-ac-LDL and binding to UEA-1. Prussian blue staining and transmission electron microscopy were used to observe the endocytosis of different SPIO concentrations in EPCs, and CCK-8 was used to detect proliferation of cells transfected with different concentrations of SPIO. T2 weighted imaging (T2WI) signals from magnetic resonance imaging after SPIO endocytosis were compared. Positive rates of CD133, VEGFR-2, and CD34 on sorted mononuclear cells were 68.2±3.8, 57.5±4.2, and 36.8±6.5%, respectively. The double-positive expression rate of CD34 and VEGFR-2 was 19.6±4.7%, and 83.1±10.4% of cells, which showed the uptake of Dil-ac-LDL and binding with UEA-1. The labeling efficiencies of SPIO at concentrations of 25 and 50 μg/mL were higher than for 12.5 μg/mL. The proliferation of cells was not influenced by SPIO concentrations of 12.5 and 25 μg/mL. After labeling, the T2WI of EPCs was reduced. The concentration of 25 μg/mL SPIO had high labeling efficiency detected by magnetic resonance imaging (MRI) without decreased EPCs viability.